IT IS FREE ART FOR FOOTBALL SOCCER-ART? A REFLECTION OF THE CONCEPT ABOUT PRODUCTS TALK OF BRAZIL NATIONAL FOOTBALL POST AMERICA CUP 2007. (Fiep Bulletin - online, 2013)
The Brazilian team football carries a football identity marked by vehicles of communication as having a commitment to a style of game known as football-art rather than a football-force itself to a European style. However, this concept is confused with another pointing the football as a kind of art, regardless of its features of play. Thus, this short article intends to move these conceptualizations dichotomous analyzing how the sports media itself intends to present the evidence in this debate, both in the radicalization of 'vs' as in its elimination. To this end, the writing divided into two stages with the first dialogue on extending the concept of art after modernism - not necessarily post-modern - that is what the sport and, consequently, football, is a kind of art the art and not be only linked to a style of playing football. In the second part looking empirically map and consider, even in summary form, the way that the media part of the construction of these offices in speeches made news in the newspaper Zero Hora / RS and Folha de Sao Paulo / SP, a total of five edits, after winning the America Cup 2007 by selected Brazilian. Football and art, soccer-art, football is art: improbability language or conceptual confusion?
Keywords: Art; Soccer; Brazilian Team